Determining the Content of Induction Programs to Improve Instructional Performance: A Case in Seoul, Korea - Cho, DaeYeon; Kwon, Dae-Bong (Alberta Journal of Educational Research, 2004)
This study represents an initial effort to determine the content of induction programs to improve beginning teachers' instructional performance. The study investigated the perception of beginning teachers' instructional performance problems and explored its relationships with demographic characteristics such as years of teaching experience and grade level. Two hundred, eighty-nine beginning teachers who were in their first four years of teaching experience in Seoul, Korea were analyzed. Results revealed (a) teaching students with special needs and with learning disabilities needs to be addressed as the most essential contents of induction programs; (b) unlike other items, these two items as instructional performance problems tend to be critical as years of teaching experience increase; (c) induction programs need to be continued for at least two years; and (d) no significant difference was found between new elementary teachers and new secondary teachers. Finally, the study includes some implications on practice and on future research.